산림골재 내 불소의 지질학적 분포 연구 - 정영일(Yeong-Il Jeong); 김건기(Kun-Ki Kim); 김순오(Soon-Oh Kim); 이상우(Sang-Woo Lee); 이진영(Jin-Young Lee) (자원환경지질, 2024)
This study was conducted to investigate the geological distribution characteristics of fluorine in rocks, which can be a major resource of forest aggregates in Korea. Samples of forest aggregates were collected from 224 sites in 22 cities and counties for this study. The national background concentration was 344 mg/kg, which was significantly lower than the average fluorine concentration of crustal, which was 625 mg/kg, and slightly higher than the average fluorine concentration of world soil, which was 321 mg/kg. In terms of region and tectonic structure, fluorine concentrations were investigated to be highest in Gyeonggi-do(394 mg/kg) and Gyeonggi massif(396 mg/kg), respectively. The concentration distribution by the origin of the parent rock was in the order of metamorphic rock(362 mg/kg) > sedimentary rock(354 mg/kg) > igneous rock(328 mg/kg), and the concentration distribution by geologic ages was the highest in the Paleozoic at 394 mg/kg. The concentration distribution by rock types was in the order of diorite(515 mg/kg) > gneisses(377 mg/kg) > schists(344 mg/kg) > phyllite(306 mg/kg) > granites(305 mg/kg) > quartz porphyry(298 mg/kg). Consequently, it is speculated that gneisses and schists, Precambrian metamorphic rocks in the Gyeonggi massif that forms the crust of Gyeonggi-do, contain high fluorine concentrations. 본 연구는 우리나라 산림골재 주요 공급원이 될 수 있는 암석 내 불소의 지질학적 분포 특성을 조사하기 위해 22개 시군의 224개 지점에서 산림골재(암석) 시료를 채취하여 불소 농도를 조사하였다. 전국 불소 배경농도는 344 mg/kg으로 암석의 지각 평균불소 농도인 625 mg/kg 보다 현저히 낮으며, 세계 토양 평균 불소 농도인 321 mg/kg 보다는 다소 높았다. 권역별 농도분포는 경기도 394 mg/kg, 강원도 336 mg/kg, 충청도 318 mg/kg, 경상도 289 mg/kg, 전라도 271 mg/kg 순서로 조사되었다. 지체구조에 의한 농도분포는 경기육괴가 396 mg/kg 으로 가장 높았으며, 퇴적분지/화산대인 울릉도가 349 mg/kg, 옥천습곡대 291 mg/kg, 영남육괴 281 mg/kg, 경상분지 259 mg/kg 순서로 높았다. 모암의 성인에 의한 농도분포는 변성암이 362 mg/kg 으로 가장 높았으며, 퇴적암 354 mg/kg, 화성암 328 mg/kg 순서로 조사되었다. 지질시대에 의한 농도분포는 고생대가 394 mg/kg 으로 가장 높았으며, 트라이아스기 391 mg/kg, 선캠브리아시대 368 mg/kg, 쥐라기 359 mg/kg, 시대미상 324 mg/kg, 제4기 314 mg/kg, 백악기 304 mg/kg 순서로 높았다. 암종에 따른 불소 농도분포는 섬록암이 515 mg/kg 으로 가장 높았으며, 편마암류 377 mg/kg, 편암류 344 mg/kg, 천매암 306 mg/kg, 화강암류 305 mg/kg, 석영반암 298 mg/kg 순서로 조사되었다. 본 연구결과를 종합해보면 경기도 지역의 지각을 이루는 경기육괴 내 선캠브리아시대 변성암인 편마암류와 편암류가 높은 농도의 불소를 함유하고 있음을 알 수 있다.